Influence of selenium and vitamin E supplementation on energy metabolism in horses used in policing activity - da Fonseca, Leandro Abreu; Gonçalves, Roberto Calderon [UNESP]; Ribeiro Filho, José Dantas; Girardi, Fabricia Modolo; Filho, Wilson Pinheiro Carvalho; Dias, Domingos Cachineiro Rodrigues; Bento, Lucas Drumond (Springer Nature, 2016)
This study evaluated the effect of supplementation with selenium and vitamin E on some blood variables in 11 adult male horses used in policing activity. Each animal was treated with 2.8 mg/400 kg of selenium and 2.000 UI/400 kg of vitamin E of body weight, orally, for a period of 30 days. On days 0 (before) and 30 (after), the animals were assessed, and blood samples were obtained before and after exercise. Glucose and lactate and plasma cortisol and serum insulin were determined. On day 0, serum cortisol concentrations were 56.8 ± 12.1 ng/ml and 43.4 ± 19.2 ng/ml, plasma lactate were 6.2 ± 0.7 mg/dl and 12.3 ± 9.2 mg/dl, serum glucose levels were 69.2 ± 5.2 mg/dl and 77.5 ± 6.6 mg/dl, and serum insulin were 3.1 ± 5.1 μUI/ml and 1.5 ± 1.6 μUI/ml, respectively, before and after exercise (M1 and M2). On day 30, serum cortisol concentrations were 55.6 ± 15.6 ng/ml and 27.6 ± 12.2 ng/mL, plasma lactate were 7.0 ± 0.9 mg/dl and 8.4 ± 1.7 mg/dl, plasma glucose were 76.0 ± 4.1 mg/dl and 77.1 ± 8.9 mg/dl, and serum insulin were 3.3 ± 6.9 μUI/ml and 2.1 ± 3.7 μUI/ml, respectively, before and after exercise (M1S and M2S). As a result of the exercise, it was shown a reduction in serum insulin and an increase in plasma lactate and glucose. Supplementation with selenium and vitamin E resulted in decreased levels of cortisol and lactate after physical activity, possibly indicating that supplementation contributed to better utilization of plasma glucose and improved adaptation to physical exercise.
Keywords: Biochemistry; Equine; Exercise; Selenium; Vitamin E